Unusual location of calcifying epithelial odontogenic tumor - Burak Cankaya; Sabri Cemil İşler; Aydın Gümüşdal; Begüm Genç; Cavanşir Asadov (Wolters Kluwer Medknow Publications, 2019)
Calcifying epithelial odontogenic tumor (CEOT), also known as Pindborg tumor, is locally aggressive and rare odontogenic epithelial neoplasm. It is mostly located in the posterior mandible. Maxillary occurrence is extremely rare, and this location leads the lesion to become more aggressive and rapidly involves to the surrounding tissues. Treatment of the lesion has a variety of choice due to location of the lesion, rapid invasion, proximity to vital structures, and early diagnosis. We present clinical, radiographic, and histopathologic examinations and surgical operation of a CEOT in the alveolar process between maxillary first and second molar roots.